2013
DOI: 10.1073/pnas.1308246110
|View full text |Cite
|
Sign up to set email alerts
|

Newborn chickens generate invariant object representations at the onset of visual object experience

Abstract: To recognize objects quickly and accurately, mature visual systems build invariant object representations that generalize across a range of novel viewing conditions (e.g., changes in viewpoint). To date, however, the origins of this core cognitive ability have not yet been established. To examine how invariant object recognition develops in a newborn visual system, I raised chickens from birth for 2 weeks within controlled-rearing chambers. These chambers provided complete control over all visual object experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 46 publications
4
116
6
Order By: Relevance
“…Hence, a first explanation for the decrease of the predisposed preference for the stuffed hen observed in some chicks is the absence of feedback from the stimulus. Second, chicks search exposure to novel stimuli before the filial imprinting process is terminated, likely to form a more comprehensive representation of it that enables recognition from novel points of view353637. Consistent evidence has shown that, especially in the early stages of imprinting, the tendency to approach the familiar object can be temporarily reversed (e.g 30363839…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a first explanation for the decrease of the predisposed preference for the stuffed hen observed in some chicks is the absence of feedback from the stimulus. Second, chicks search exposure to novel stimuli before the filial imprinting process is terminated, likely to form a more comprehensive representation of it that enables recognition from novel points of view353637. Consistent evidence has shown that, especially in the early stages of imprinting, the tendency to approach the familiar object can be temporarily reversed (e.g 30363839…”
Section: Resultsmentioning
confidence: 99%
“… Average recognition performance for the present study and for Experiment 1 from Wood (2013). The same two virtual objects were used in both studies.…”
Section: Resultsmentioning
confidence: 99%
“…The animations are presented in electronic supplementary material, movies S1-S3. The object appeared for an equal amount of time on the left and right display walls, switching walls every 2 h. The virtual objects were modelled after those used in previous studies that tested for invariant object recognition in adult rats [7,8] and newborn chicks [12][13][14]. Half of the chicks were imprinted to each of the two objects, with the other object serving as the novel object.…”
Section: Iii) Proceduresmentioning
confidence: 99%